A Whole Lot of Shaking — Seismic Load Considerations in Thickener Design - Hooimeyer, E; Rosart, J (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
In paste and thickened tailings disposal, one of the most structurally significant components is the thickener. When calculating the strength of the supporting structure, the effects of seismic activity become an important design consideration, particularly in countries prone to high activity. Thickener tanks can hold in excess of 10 million litres of slurry, having masses greater than 15,000 tonnes. Thus, even in relatively low seismic zones, a thorough understanding of the seismic behaviour of these tanks is critical when it comes to structural integrity and safety. A further consideration is the financial and operability benefits when examining structure weight and footing design. The influence of ground conditions on the magnitude of forces is often overlooked. It is commonly known that more earthquake damage occurs in softer soils than rock. This paper will explore different ground conditions and show how site-specific ground data can be used to make informed decisions on thickener selection. Another significant consideration is thickener shape. A parallel here is building design for earthquake sensitive regions. Natural frequencies are evaluated to see if structures are prone to damage, showing the critical geometry one should avoid. In thickeners, sizing and shape is driven by process decisions. There are, however, alternative shapes that can perform equally well. This paper will explore thickener shapes and the suitability for various seismic conditions. It will also explore support methods and their response to seismic loads.